2020
DOI: 10.1093/cid/ciaa1149
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Bocavirus Respiratory Tract Infection in Hematopoietic Cell Transplant Recipients

Abstract: Background Limited data exist regarding the impact of human bocavirus (BoV) in hematopoietic cell transplant (HCT) recipients. Methods In a longitudinal surveillance study among allogeneic HCT recipients, pre-HCT and weekly post-HCT nasal washes and symptom surveys were collected through day 100, then at least every 3 months through 1 year post-HCT at the Fred Hutch (2005-2010). Samples were tested by multiplex semi-quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In contrast, the proportion of imaging results confirmed that pneumonia in the single-infection group was higher than that in the mixed-infection group, and there was a significant difference between the two groups. In addition, low Ct-values of HBoV-positive patients had a lower rate of lung markings observed than high Ct-values of HBoV-positive patients (31.58 vs. 64.86%, P = 0.0018), suggesting that a single HBoV infection may not aggravate lung disease in nonsevere patients (He et al, 2021 ; Ogimi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the proportion of imaging results confirmed that pneumonia in the single-infection group was higher than that in the mixed-infection group, and there was a significant difference between the two groups. In addition, low Ct-values of HBoV-positive patients had a lower rate of lung markings observed than high Ct-values of HBoV-positive patients (31.58 vs. 64.86%, P = 0.0018), suggesting that a single HBoV infection may not aggravate lung disease in nonsevere patients (He et al, 2021 ; Ogimi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scarce data are available concerning the relationship between HBoV and respiratory disease in HSCT recipients. In a prospective surveillance study on pediatric and adult HSCT recipients, 195 hBoV was infrequently detected (0.5%). In contrast, Piñana et al showed hBoV isolation in 8% of allo-HCT recipients developing respiratory viral infections over a period of 30 months.…”
Section: Hbovmentioning
confidence: 99%
“…It has been suggested that hBoV detection in the respiratory tract is associated with watery eyes and rhinorrhea. 195 Currently there is no available antiviral agent nor novel molecule in development against hBoV.…”
Section: Hbovmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported a higher prevalence of such infections during winter and spring (14), while others reported a higher prevalence in the first summer days (15). However, several researchers reported no clear seasonal pattern (16). In Iran, HBoV infection is said to be seasonal, with a higher incidence in winter and late autumn (12).…”
Section: Discussionmentioning
confidence: 99%